Potamonautes gorongosa, a new species of potamonautid freshwater crab (Decapoda, Brachyura) from Mozambique, southeastern Africa - Cumberlidge,Neil (2016)
Abstract A new species of the freshwater crab genus Potamonautes MacLeay, 1838, is described from Gorongosa National Park in Sofala Province, Mozambique, southern Africa. Potamonautes gorongosa, new species, is morphologically and phylogenetically distinct from the other species of Potamonautes found in Mozambique and nearby countries, and is most closely related to Potamonautes mutareensis Phiri and Daniels, 2013, from eastern Zimbabwe. The new species differs from this species and its other congeners by a unique combination of morphological characters of the first gonopod, the anterior sternum, third maxilliped, and the major cheliped. Illustrations of P. gorongosa new species are provided, and differences with other species found in Mozambique and southeastern Africa are discussed.